Successful liver transplantation in a critically underweight patient: a case report - K. O. Semash; T. A. Dzhanbekov; R. A. Ibadov (Вестник трансплантологии и искусственных органов)
Introduction. Living-donor liver transplantation (LT) is a viable and effective treatment option for patients with end-stage liver disease. Cachexia is widely recognized in medical literature as a risk factor affecting patient sur vival after LT. However, there are relatively few reports on LT in adult patients with critically low body weight.Materials and methods. The clinical case of successful LT in a critically underweight patient (BMI 12.9 kg/m2) is presented.Results. The patient’s pre-transplant preparation included intensified enteral and parenteral nutrition, albumin and fresh frozen plasma transfusions, diuretic therapy, multivitamins, symptomatic treatment, and structured exercise. At the time of transplantation, the recipient’s MELD (Model for End-Stage Liver Disease) score was 22. In the postoperative period, the patient had multiple complications, reflected by a comprehensive complication index (Comprehensive Comprehensive) score of 99. Multicomponent rehabilitation was implemented. The patient was discharged 30 days after LT. During a 17-month follow-up, graft function remained satisfactory.Conclusion. Our experience, supported by literature data, indicates that cachexia in liver transplant recipients is associated with a higher overall complication rate after LT. Patients with low body weight require careful pre-transplant preparation, including intensive nutritional support and exercise programs. Successful treatment of such patients is feasible only in a multidisciplinary hospital or a transplant center with extensive expertise in managing complex cases.